Degressively proportional functions using the example of seat distribution in the European Parliament - Dniestrzański, Piotr (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
This article presents an example of the current problem from the borders of economics and politics, which can be used in mathematics courses for economics majors. This problem is the distribution of seats in the European Parliament among the member states of the European Union, and the principle of degressive proportionality formulated for this purpose in the legislation.
Didactics of Mathematics, 2012, Nr 9 (13), s. 35-42
Keywords: degressive proportionality; mathematics teaching